Engagement, Technology, and Mathematics: Students’ Perceptions - Catherine Attard (Southeast Asian Mathematics Education Journal, 2014)
Many schools are investing significant funds in technology in the hope that it will address declining engagement with mathematics and improve students’ learning outcomes. This paper presents data from two studies and explores students’ perceptions of technology use during mathematics lessons and their resulting engagement. Results from the two studies suggest some relationship between the ways in which technologies are incorporated into mathematics lessons, and teacher experience and expertise.